Non-invasive evaluation of placental blood flow: lessons from animal models. Issue 3 (March 2017) - Mourier, E; Tarrade, A; Duan, J; Richard, C; Bertholdt, C; Beaumont, M; Morel, O; Chavatte-Palmer, P
Abstract : In human obstetrics, placental vascularisation impairment is frequent as well as linked to severe pathological events (preeclampsia and intrauterine growth restriction), and there is a need for reliable methods allowing non-invasive evaluation of placental blood flow. Uteroplacental vascularisation is complex, and animal models are essential for the technical development and safety assessment of these imaging tools for human clinical use; however, these techniques can also be applied in the veterinary context. This paper reviews how ultrasound-based imaging methods such as 2D and 3D Doppler can provide valuable insight for the exploration of placental blood flow both in humans and animals and how new approaches such as the use of ultrasound contrast agents or ultrafast Doppler may allow to discriminate between maternal (non-pulsatile) and foetal (pulsatile) blood flow in the placenta. Finally, functional magnetic resonance imaging could also be used to evaluate placental blood flow, as indicated by studies in animal models, but its safety in human pregnancy still requires to be confirmed.